ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER PADA LAGU DAERAH SASAK SISWA SEKOLAH DASAR - Parida Zohriatun; RR. Sri Setyawati Mulyaningsih; Lalu Mas’ud (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This study aims to determine the values of character education in Sasak folk songs (Kadal Nongak, Inak Tegining Amak Teganang, and Tiang Tunas Pamit)for the third graders of Setuta state elementary school. This type of research is qualitative research. Techniques for collecting data were by observation, interviews, and documentation. Based on the results of the research and discussion, it can be concluded that the values of character education in Sasak folk songs (Kadal Nongak, Inak Tegining Amak Teganang, and Tiang Tunas pamit) could be obtained from those Sasak folk songs. This was evidenced by the existence of activities carried out in the school environment such as religious values in Sasakregional songs carried out trough religious activities (Friday imtaq). Discipline values in Sasak folk song are carried out through flag ceremonies and SKJ gymnastics. The value of caring for the environment in Sasak folk song is carried out trough pickets according to the schedule, throwing trash in its place, picking up if you see trash scattered, carrying out community service. The value of responsibility in Sasak folk songs is carried out through giving homework, complying with the regulations that apply at school. Honest values in sasak folk songs are carried out through not cheating on cheating on friends during tests.